2013
DOI: 10.1159/000351159
|View full text |Cite
|
Sign up to set email alerts
|

Indeterminate and Erroneous Fine-Needle Aspirates of Breast with Focus on the ‘True Gray Zone': A Review

Abstract: Objective: To review our experience and the literature on inconclusive/erroneous fine-needle aspirates (FNAs) of breast with the focus on the ‘true gray zone'. To describe the cytology, differential diagnosis, pitfalls and limitations of common and rare lesions. Study Design: We conducted a literature search focusing on breast FNAs with statistical data of C3 and C4 categories including false-positive and false-negative cases. Similar data from 2003 to 2009 was obtained from our institution. Results: C3 and C4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(35 citation statements)
references
References 171 publications
(131 reference statements)
5
30
0
Order By: Relevance
“…We, like others have shown a heterogeneous mix of pathological outcomes during the follow up of C3 (5,(9)(10)(11)(12)(13)(14). In our earlier study, of 230 atypical (C3) cases, we found 37.4% to be malignant on follow-up and the remaining 62.6% yielded benign outcomes.…”
Section: Introductionsupporting
confidence: 51%
See 2 more Smart Citations
“…We, like others have shown a heterogeneous mix of pathological outcomes during the follow up of C3 (5,(9)(10)(11)(12)(13)(14). In our earlier study, of 230 atypical (C3) cases, we found 37.4% to be malignant on follow-up and the remaining 62.6% yielded benign outcomes.…”
Section: Introductionsupporting
confidence: 51%
“…al. note the finding of tubular structures should be interpreted with caution as they can also be found in fibroadenomas, sclerosing adenosis and complex sclerosing lesions but are more frequently observed in tubular carcinoma (9,22). Kundu also warns against over-interpreting tubular structures as they can mimic malignancy in cases of sclerosing adenosis but states that these should also contain myoepithelial cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies have documented fibroadenoma as being one of the most commonly misdiagnosed lesions that appear as the grey zone lesions. 14,15 Fibroadenoma with atypia was reported in 2 cases. These on histopathology were diagnosed as usual ductal hyperplasia and duct carcinoma in situ (Figure 1a and 1b).…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous factors that contribute to the indefinite, FN and FP categories. 15 These include: (1) technical difficulties where the smears are limited by cellularity or obscured by drying artefact and or blood, (2) inexperience or unfamiliarity of the pathologist with the cytologic features of breast FNAs and (3) the overlap of cytologic features of certain benign and malignant conditions due to the nature of the lesion (true grey zone).…”
Section: Discussionmentioning
confidence: 99%